Chinese foreign policy : an introduction - Lanteigne, Marc (Abhingdon Routledge, 2019)
This updated and expanded fourth edition of Chinese Foreign Policy seeks to examine the decision-makers, processes and rationales behind China's expanding international relations as well as offering an in-depth look at China's modern global relations. Among the key issues explored in this edition are: the further expansion of Chinese foreign policy from regional (Asia-Pacific) to international interests; how the government of Xi Jinping has pursued a more confident great power foreign policy agenda; China's growing economic power in an era of global financial uncertainty and the return of protectionism; modern security challenges, including counter-terrorism, cyber-security, maritime power, military reform and modernisation, and the protection of overseas economic interests; China's shifting power relationship with the United States under President Donald Trump; the deeper engagement of Beijing with a growing number of international and regional institutions and legal affairs; cross-regional diplomacy, including updated sections on Africa, Latin America, the Middle East, and Russia/Eurasia, as well as Oceania and the Polar regions; the development of the Belt and Road Initiative as a centrepiece of China's foreign policy. This book will be essential reading for students of Chinese Foreign Policy and Asian International Relations, and highly recommended for students of diplomacy, international security and IR in general
Includes bibliographical references and index.
Keywords: China; Diplomatic relations